Potential effect of mangosteen extract incorporation into self-etch adhesive on dentin bonding - Mahdan, Mohd Haidil Akmal; Muhamad Halil, Mohd Haikal; Sulaiman, Ahmad Syahrizan; Ismail, Ikmal Hisyam; Darnis, Deny Susanti (BioMed Research Publishers, 2024)
The aim of this study was to investigate the effect of incorporation of mangosteen natural extract into self-etching primer on dentine bond strength. A total of sixty human molars were utilized for the purposes of this investigation. These molars were sectioned at the cement-enamel junction in order to create flat dentine surfaces. Three experimental primers were produced by including 0.5% Mangosteen peel extract (MPE), 0.5% Chlorhexidine (CHX), or 0.5% Grape seed extract into Kerr Optibond Versa (Kerr, USA). The initial Kerr primer was utilized as the control in the experiment. Subsequently, all specimens were subjected to bonding using Kerr Optibond Versa adhesive. The resin composite was then sequentially applied in four layers to create the build-up. Following this, the specimens were immersed in water and housed in a 37 oC incubator for a duration of 24 hours. The specimens that were bonded together were subsequently divided into beams of 2x2 mm in size and were then subjected to micro tensile bond testing (μTBS). The debonded samples were examined using a scanning electron microscope (SEM) in order to analyze the fracture mode. The results of the study indicate that there were statistically significant differences in the microtensile bond strength (μTBS) between the experimental and control groups, as determined by a Two-way Analysis of Variance (ANOVA) test (p<0.05). The post-hoc comparison test revealed a substantial increase in microtensile bond strength (μTBS) with the integration of MPA, as compared to the other two groups (p<0.001). In conclusion, the inclusion of MPE in the Kerr Optibond Versa primer has a positive impact on the instant bond strength of a dental restoration.